Multidimensional analysis of embeddedness and cooperation in a cluster – a literature and empirical study - Marzena Frankowska (Journal of Entrepreneurship, Management and Innovation)
Cooperation of enterprises within inter-organizational networks is a complex research and cognitive area due to the multidimensional nature of cooperation, which is often a mixture of motives, intentions, goals and operating conditions. Literature studies have revealed the so far very meager and scattered work in the field of embedding cooperation between enterprises in inter-organizational networks, which definitely does not sufficiently describe the impact of the context of collaboration on enterprise cooperation. The main aim of the article was to understand and explain, on the basis of the concept of embeddedness, whether there are relations between the participation of enterprises in a cluster-type inter-organizational network (embeddedness and its dimensions) and their cooperation in the cluster. Implementation of research goals required the development of a research process covering three stages. The essence and dimensions of embeddedness of cooperating enterprises in inter-organizational networks (structural, relational, social, positional, territorial, geographical, spatial, institutional, ecological, political and temporal) were determined. Next, a survey of European cluster managers (study 1) on cooperation in a cluster was carried out in order to better understand the dimensions of embeddedness of enterprises cooperating in clusters (qualitative research, IDI). In the next stage, a survey of cluster enterprises was carried out (study 2) to determine the relations between their embeddedness in the cluster and cooperation with other cluster companies (quantitative research, CAWI). Then, triangulation of data sources, research methods and context was used. As a result, it was established that four dimensions of embeddedness are of key importance for cooperating enterprises embedded in the cluster, namely: structural, geographical, institutional and relational. Moreover, the results of the research show that there is a positive relation between embedding enterprises in the cluster and their cooperation.